PEMBERDAYAAN KADER DALAM PENERAPAN CPP-ACP UNTUK MENCEGAH KARIES DINI PADA ANAK DI KELURAHAN KARSAMENAK, KAWALU TASIKMALAYA - Rismayani, Lina; Suharja, Eliati Sri (LPPM Universitas Bina Bangsa, 2024)
ECC data for the 3–4-year age group in Indonesia in 2018 was 81.5%, indicating that only 18.5% were caries-free. ECC requires preventive measures to prevent caries from worsening, in order to achieve the goal of a healthy, caries-free Indonesia by 2030 with a minimum DMFT of 1.14 at the age of 12 years. The application of CPP-ACP can further prevent demineralization in children. CPP-ACP can neutralize saliva pH to normal levels, thereby supporting the remineralization of teeth. The proposed solution in this activity is to introduce a caries prevention program that can be implemented in Posyandu. This can be achieved by empowering cadres in the application of CPP-ACP. The method used is to empower cadres in applying CPP-ACP by providing training (ToT). Evaluation results show that there are significant differences between the pre-test and post-test results of knowledge, skills and saliva pH. Empowering dental health cadres has been proven to increase their knowledge and abilities in applying CPP-ACP as an effort to prevent caries from an early age in toddlers at Posyandu. The majority of the results from the pH examination of the saliva of posyandu toddlers returned to normal after the application of CPP-ACP by the cadre